1964
DOI: 10.1126/science.145.3634.835
|View full text |Cite
|
Sign up to set email alerts
|

Depth Perception in Sheep: Effects of Interrupting the Mother-Neonate Bond

Abstract: Twin lambs were divided into two groups: an unmothered group consisting of one of each pair of twins separated from its mother at birth, and a mothered group consisting of the other member of each pair reared by its mother. Lambs in both groups were placed individually on a "visual cliff" once every hour. In all instances lambs in the mothered group exhibited "cliff avoidance" behavior before those in the unmothered group. In another experiment, mothered lambs were fitted with translucent goggles for half the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…To facilitate cattle movement, illumination should be even, and there should be no sudden changes in floor level or texture. Even though ruminant animals have depth perception (Lemmon and Patterson, 1964), their ability to perceive depth at ground level while moving with their heads up is probably poor. Hutson 0985b) suggests that there may be an extensive blind area at ground level and moving livestock may not be able to use motion parallax or retinal disparity cues to perceive depth.…”
Section: Cattle Perceptionmentioning
confidence: 99%
“…To facilitate cattle movement, illumination should be even, and there should be no sudden changes in floor level or texture. Even though ruminant animals have depth perception (Lemmon and Patterson, 1964), their ability to perceive depth at ground level while moving with their heads up is probably poor. Hutson 0985b) suggests that there may be an extensive blind area at ground level and moving livestock may not be able to use motion parallax or retinal disparity cues to perceive depth.…”
Section: Cattle Perceptionmentioning
confidence: 99%
“…The visual cliff consisted of a raised surface, half covered by Plexiglas and half covered by solid materials, with a board in the middle, which gave the impression of a large drop in height on the glassed (deep) side and of a short drop in height on the solid (shallow) side. All land-dwelling species (including human infants, rats, cats, goats, pigs, dogs, monkeys, lambs, and chickens) tested on the apparatus showed an overall avoidance of depth, which provided evidence both of capacity for depth discrimination and of the existence of an apparent universal fear response when individuals are faced with a vertical drop (Lemmon & Patterson, 1964;Walk & Gibson, 1961). Because the individuals tested were juveniles, results can be interpreted as evidence of an innate rather than of a learned fear of heights.…”
mentioning
confidence: 93%
“…Because the individuals tested were juveniles, results can be interpreted as evidence of an innate rather than of a learned fear of heights. However, Lemmon and Patterson (1964) have suggested that the development of depth perception in juvenile animals may be affected by the mother–neonate bond.…”
mentioning
confidence: 99%
“…If cattle look down and see a steep drop-off, they often refuse to enter 10 . Ruminants have depth perception 11 .…”
Section: Discussionmentioning
confidence: 99%